2018
DOI: 10.1002/ijop.12486
|View full text |Cite
|
Sign up to set email alerts
|

Perceived emotion suppression and culture: Effects on psychological well‐being

Abstract: Whether the negative effects of emotion suppression on psychological well-being are applicable cross-culturally is a long-debated topic. The present study attempted to shed light on this debate, focusing on the effects of perceived emotion suppression and examining the psychological processes leading from perceived emotion suppression to lower psychological well-being. We used a scale manipulation to lead 196 American and 213 Chinese participants to perceive themselves as having suppressed their emotions to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…This suggests that having a collectivist orientation emphasizes the willingness to invest personal resources in terms of work engagement and organizational citizenship behavior. Thus, this study responds to the call of scholars to explore the context and boundary conditions surrounding employee well-being [80,81].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that having a collectivist orientation emphasizes the willingness to invest personal resources in terms of work engagement and organizational citizenship behavior. Thus, this study responds to the call of scholars to explore the context and boundary conditions surrounding employee well-being [80,81].…”
Section: Discussionmentioning
confidence: 99%
“…To detect an effect size found in related past research (Cohen’s d = 0.40; Kwon & Kim, 2017) with 80% power at the alpha level of .05, 272 American college students (181 women) at a public university in the northeastern United States and 282 Hong Kong Chinese college students (123 women) from a university in Hong Kong were recruited.…”
Section: Methodsmentioning
confidence: 99%
“…To detect an effect size found in related past research (Cohen's d = 0.40; Kwon & Kim, 2017) with 80% power at the alpha level of .05, 272 American college students (181 women) at a public university in the northeastern United States and 282 Hong Kong Chinese college students (123 women) from a university in Hong Kong were recruited. American participants' ethnicity was varied (White or Caucasian = 44.9%, Black or African American = 6.6%, American Indian = 0.4%, Asian American = 22.1%, Hispanic or Latino American = 10.7%, and Other = 15.5%).…”
Section: Participantsmentioning
confidence: 99%
“…Emotional suppression can be viewed as an emotion-based coping strategy because it is focused on inhibiting the expression of emotion. Studies have demonstrated that emotional suppression is associated with negative physical effects (e.g., increased blood pressure; Gross & Levenson, 1993; Roberts, Levenson, & Gross, 2008), reduced positive affect (Abler et al, 2010; Gross & John, 2003; Kwon & Kim, 2018; Larsen et al, 2012), and lower life satisfaction (Gross & John, 2003; Kwon & Kim, 2018; Sheldon, Ryan, Rawsthorne, & Ilardi, 1997). Emotional suppression is also associated with a reduction in one’s ability to attend to and process social information (Egloff, Schmukle, Burns, & Schwerdtfeger, 2006; Hayes et al, 2010; Moore & Zoellner, 2012; Richards & Gross, 2000).…”
Section: Introductionmentioning
confidence: 99%